Atypical course of type 1 diabetes mellitus in a patient with Ollier's disease - a case report - Anna Kochanowska; Kinga Knop; Zuzanna Piasecka; Maria Kowalczuk; Grzegorz Rudzki (Journal of Education, Health and Sport, 2022)
Background